APPLICATION OF MOLDEX3D FOR MODELING THE INJECTION MOLDING PROCESS OF A SHOE SOLE MADE OF VISCOUS POLYMER AND ANALYSIS OF FILLING PARAMETERS - POLISHCHUK, OLEG; KUNTSOV, OLEKSANDR; PIDHAICHUK, SVITLANA; ZAHUROVSKYI, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents the application of the Moldex3D computer-aided engineering (CAE) software for detailed simulation of the injection molding process of a shoe sole manufactured from a viscous polymer melt. The main objective of the study is to demonstrate how Moldex3D can be used not only as a visualization tool, but as a virtual laboratory that supports engineering decisions at the early stages of mold and process design. The workflow includes CAD model preparation of the shoe sole geometry, import and healing of surfaces, finite element mesh generation with local refinement in thin sections and near the gates, and assignment of rheological, thermal and processing data for the selected polymer grade.Numerical analysis is performed for the filling stage of the molding cycle. The software provides contour plots and vector fields for the spatial distribution of flow velocity, viscosity, frozen-layer ratio, shear rate and individual velocity components in the mold cavity. These results make it possible to identify regions of accelerated and decelerated flow, early solidification near colder mold walls, and areas with excessive shear loading that may lead to material degradation. Special attention is paid to the detection of risk zones for typical injection molding defects, such as short shots, weld lines, air entrapment, local sink marks and non-uniform packing.It is shown that Moldex3D simulations give a physically consistent picture of the filling process and can be effectively used to perform preliminary optimization of injection pressure, melt and mold temperatures, filling time and runner/gate configuration without manufacturing experimental molds. The results confirm the usefulness of CAE-based simulation as an integral part of the design and engineering cycle for polymer shoe soles, helping to reduce development time, material consumption and the number of trial-and-error iterations on real equipment.
Keywords: injection molding; shoe sole; polymer melt; viscous flow; Moldex3D; finite element simulation; filling velocity; frozen layer; shear rate